Increasing the Information Quality of social media on the Political Involvement of Millennials Using Social Media - Syabillah Laviola Adha; Yolanda Masnita (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Political involvement, namely community activity in influencing the methods of preparing and implementing public policies, as well as participating in choosing government leaders. Social media is widely used as a place to engage in political activities. This study aims to examine the quality of social media information, social media reputation, trust, use of social media, and millennial political involvement. The instrument of this research is using a questionnaire created using a Google form that is distributed online. The respondents of this study are millennials. This study contributes to the inconsistency test between social media information quality variables and political involvement. The results of the study prove that there is an influence between the variables use of social media and political involvement. This study also concluded that most of the millennial generation use social media for 3 hours/day to seek information and communicate. Finally, this research can find that the use of social media affects political involvement.